Neo-endogenous revitalisation: Enhancing community resilience through art tourism and rural entrepreneurship. (January 2023) - Qu, Meng; Zollet, Simona
Abstract: The decline and socio-economic stagnation of rural communities is a growing concern across the world. To promote community resilience, art- and creativity-based strategies are emerging as important means for rural revitalisation. This study adopts a neo-endogenous perspective to examine how socially engaged art can represent an effective tool for revitalising communities and strengthening their resilience. We examine the case of Japan's Setouchi Triennale, an international art festival which aims at revitalising twelve small islands by promoting socially engaged art and festival tourism. This mixed methods research focuses on the three islands characterised by the best revitalisation outcomes. The tourism opportunities and increased place recognition resulting from the exogenous art festival initiative triggered endogenous community responses in terms of increased entrepreneurship and social innovation, facilitating the emergence of neo-endogenous revitalisation processes. At the same time, different islands are characterized by different response mechanisms, which depend on the initial resources and features of each island. Exogenous, endogenous, and neo-endogenous elements are therefore all necessary to increase rural resilience. Successful neo-endogenous revitalisation through socially engaged art, however, requires long-term co-creation between exogenous art development and endogenous community activities. Highlights: Art and creativity are important drivers of rural resilience in the knowledge economy. Socially-engaged art festivals with an explicit rural revitalisation mission are gaining popularity. The opportunities and resources brought by these exogenous initiatives can trigger endogenous community responses in terms of increased entrepreneurship and social innovation. This facilitates the emergence of neo-endogenous co-revitalisation processes. Exogenous and endogenous elements are both necessary to increase rural resilience. Although neo-endogenous processes support revitalisation, the mechanisms through which they occur depend on the initial resources and characteristics of each community.